Key Statistics and Trends in International Trade 2018 - United Nations Conference on Trade; Development (United Nations, 2019)
This annual publication monitors the trends of international trade in goods and services in the medium term. The series is part of a larger effort by UNCTAD to analyse trade-related issues of particular importance for developing countries.